IDENTIFIKASI PENYEBAB KEJADIAN LUAR BIASA KOLERA DI PAPUA TERKAIT KONTAK JENAZAH DAN SANITASI - Nelly Puspandari; Kambang Sariadji; Melati Wati (Widyariset, 2010)
Cholera outbreak in District Nabire and Paniai, Papua province in May to August in 2008 killed 105 people. The aim or the research was to describe the infection of cholera through human corpse and sanitation. Bacteriological examination was conducted on rectal swabs from diarrhea victims and theirs contacts and sources of water from three places. The samples were cultured, isolated, examined the serology test in the Bacteriology laboratory of the Center for Research and Pharmaceuticals Biomedical Agency, National Institute of Health and Research Development Jakarta. The results showed that the occurrence outbreak in Papua Province was caused by Ogawa, subtype of Vibrio cholera that also contaminated the water sources. The Culture of Papuan, hugging and kissing the human corpse made the evidence of cholerae worst.